2012
DOI: 10.1063/1.4767688
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface oxidation on plasmon resonance in monolayer of gold and silver nanoparticles

Abstract: Surface plasmon resonance of gold and silver nanoparticle (NP) layers is investigated by the experiment as well as simulations. Although the good agreement was found for gold NP film, a significant mismatch in the resonance energy for silver NP film was observed. The deviation was assigned to the presence of silver oxide (Ag2O) in silver NPs. As an alternative to the NP size-dependent Drude model, the analysis based on effective medium approximation for refractive index of Ag-Ag2O material system is carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 31 publications
4
71
1
Order By: Relevance
“…In addition, the intensity of the plasmon resonance is also affected by the oxide producing the attenuation of the signal due to the dielectric character of the oxide. However, this attenuation is not as intense as for Ag 22 and Al 23 . This is due to the lower extinction coefficient of Ga 2 O 3 compared to the other oxides 24 .…”
Section: Resultsmentioning
confidence: 86%
“…In addition, the intensity of the plasmon resonance is also affected by the oxide producing the attenuation of the signal due to the dielectric character of the oxide. However, this attenuation is not as intense as for Ag 22 and Al 23 . This is due to the lower extinction coefficient of Ga 2 O 3 compared to the other oxides 24 .…”
Section: Resultsmentioning
confidence: 86%
“…Amongst, VDT is advantageous over wet chemistry routes because it can directly be used for the above mentioned applications before going for any surplus process. However, it oxidizes rapidly as soon as exposed to atmosphere [11,19,20]. It is a great challenge to deposit un-oxidized Ag NPs with the optimized size and shape which exhibits strong SPR near UV-Vis region.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of AgO at the surface level due to air annealing process would not be really a big concern for SPR. However, it leads to a red shift due to an increase of dielectric constant of the medium in which NPs are present [12,20]. AgO is wide bad semiconducting material having potential applications such as optical memories [22], filters [23] and plasmon photonic devices [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficiencies of these metals depends sensitively on the surrounding dielectric environment, and all of them, except Au and Rh, form native oxides that wrap the NP with a shell, whose thickness depends on both the metal and the environmental exposure conditions (temperature and pressure). Consequently, it is essential to understand the effect of oxidation on their UV plasmonic response [7,9,19]. Also, very recently it was shown that, since oxidation is a means to grow a dielectric shell, its control may be used to tune the plasmonic resonance of NPs [14].…”
Section: Introductionmentioning
confidence: 99%